How monoxenous trypanosomatids revealed hidden feeding habits of their tsetse fly hosts - Votypka, Jan; Petrzelkova, Klara J; Brzonova, Jana; Jirku, Milan; Modry, David; Lukes, Julius (Folia parasitologica, 2021)
Tsetse flies are well-known vectors of trypanosomes pathogenic for humans and livestock. For these strictly blood-feeding viviparous flies, the host blood should be the only source of nutrients and liquids, as well as any exogenous microorganisms colonising their intestine. Here we describe the unexpected finding of several monoxenous trypanosomatids in their gut. In a total of 564 individually examined Glossina (Austenia) tabaniformis (Westwood) (436 specimens) and Glossina (Nemorhina) fuscipes fuscipes (Newstead) (128 specimens) captured in the Dzanga-Sangha Protected Areas, Central African Republic, 24 (4.3%) individuals were infected with monoxenous trypanosomatids belonging to the genera Crithidia Léger, 1902; Kentomonas Votýpka, Yurchenko, Kostygov et Lukeš, 2014; Novymonas Kostygov et Yurchenko, 2020; Obscuromonas Votýpka et Lukeš, 2021; and Wallacemonas Kostygov et Yurchenko, 2014. Moreover, additional 20 (3.5%) inspected tsetse flies harboured free-living bodonids affiliated with the genera Dimastigella Sandon, 1928; Neobodo Vickerman, 2004; Parabodo Skuja, 1939; and Rhynchomonas Klebs, 1892. In the context of the recently described feeding behaviour of these dipterans, we propose that they become infected while taking sugar meals and water, providing indirect evidence that blood is not their only source of food and liquids.
Keywords: adenotrophic viviparity; Central African Republic; Glossina; Trypanosoma; stravovací zvyklosti; infection.; Středoafrická republika; Feeding Behavior; Trypanosomatina; Animals; Tsetse Flies; blood-feeding; Host-Parasite Interactions; bodonids; zvířata; interakce hostitele a parazita; moucha tse-tse